Religious Knowledge from the Perspective of Àyatullah Jawadi Àmuli - husayn SÙzanchi (حکمت اسرا)
Àyatullah Jawadi Àmuli is a thinker who by drawing from various fields of the Islamic intellectual tradition—such as Islamic philosophy and the principles of jurisprudence—presents a unique exposition of ‘religious knowledge’. He is of the belief that knowledge qua knowledge is a disclosure of reality and hence any true knowledge is Islamic. He further claims that an analysis of “knowledge” [cum ‘science’] in the modern period leads to the conclusion that modern sciences are not true and bona fide knowledge, insofar as they have been affected by profane philosophy. In his opinion, if we were to bring about fundamental changes in the existing sciences and come to an ‘Islamic science’, we must lend force to a particular take on ‘knowledge’ and ‘science’. Such an approach would involve first, situating the cognitive and scientific accomplishments of humanity (spanning the scope from experimental sciences to sciences such as philosophy and mysticism) within the geometry of religious knowledge, and second, establishing a particular correlation and correspondence between experimental, rational, and mystical findings on the one hand and traditional sources on the other. The crux of his perspective can be characterised by its conscious awareness of the hierarchy and multiple states of the intellect in the latter’s comprehension of the realities of the world and the extensive correlation between the intellect and tradition. The article at hand attempts to present a survey of Ay JawÁdÐ’s religious and epistemological positions with regards to profane sciences and religious knowledge.